Epidemiology of neurological diseases in older adults - Dumurgier, J.; Tzourio, C. (Revue neurologique, 2020)
Neurological diseases refer to the diseases that target the nervous system (brain, spine or nerves). They are the second leading cause of death, and the first cause of severe long-term disability in the world. The prevalence of most neurological diseases increases sharply with age, and age also modulates the impact of risk factors, clinical presentation and the natural course of these diseases. Longitudinal population-based studies provide useful insights for a better understanding of the specificities of neurological diseases in older adults by assessment of a wide range of risk factors. Rapid population aging, especially in low-income countries, presents challenges in terms of health and social care. A multidisciplinary approach is necessary to find solutions to tackle the burden of neurological diseases in older adults.